2022
DOI: 10.5140/jass.2022.39.3.87
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of Equatorial Plasma Bubbles in Ionospheric Connection Explorer/Far-UltraViolet (ICON/FUV) Limb Images

Abstract: The Far-UltraViolet (FUV) imager onboard the Ionospheric Connection Explorer (ICON) spacecraft provides two-dimensional limb images of oxygen airglow in the nightside low-latitude ionosphere that are used to determine the oxygen ion density. As yet, no FUV limb imager has been used for climatological analyses of Equatorial Plasma Bubbles (EPBs). To examine the potential of ICON/FUV for this purpose, we statistically investigate small-scale (~180 km) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…This phenomenon is also visible in prior studies, such as J. Park et al (2022). The phenomenon has been attributed to the sun's apparent location during the day and the solar terminator being nearly parallel to the QD field lines about the SAA.…”
Section: Plasma Bubble Detectionssupporting
confidence: 58%
“…This phenomenon is also visible in prior studies, such as J. Park et al (2022). The phenomenon has been attributed to the sun's apparent location during the day and the solar terminator being nearly parallel to the QD field lines about the SAA.…”
Section: Plasma Bubble Detectionssupporting
confidence: 58%
“…Consequently, the ambient density shows, in agreement with earlier research, (1) the well-known zonal wavenumber-4 structures in the EIA and (2) offequatorial enhancement above the Caribbean. As a complement to other observations from FUV disk imagers and in-situ plasma probes, ICON/FUV data are expected to be useful in EPBs studies [21].…”
Section: Ionospherementioning
confidence: 99%
“…Nevertheless, there are no known instances of climatological analysis of EPBs using Far-UltraViolet (FUV) limb imaging devices. Park et al [21] investigated the small-scale measurement of oxygen ion density observed in limb images of FUV on board the Ionospheric Connection Explorer (ICON) with the aim of confirming the feasibility of using EPBs in climatological analysis. Two-dimensional limb images of oxygen airglow are available in the 135.6 nm and 157 nm channels via ICON/FUV.…”
Section: Ionospherementioning
confidence: 99%
See 1 more Smart Citation